The relationship between professional autonomy and moral distress in ICU nurses of Guilan University of Medical Sciences in 2017 - Yeganeh, Mohammad Reza; Pouralizadeh, Moluk; Ghanbari, Atefeh (Nursing practice today, 2019)
Background & Aim: Professional autonomy is a key component of decision-making and empowerment of the nurses. However, ICU nurses sometimes experience a degree of moral distress in their decision-making but the relationship of this distress with their autonomous performance in intensive care units is unclear. The aim of this study is determining the relationship between professional autonomy and moral distress of ICU nurses. Methods & Materials: In this correlational cross-sectional study, 180 ICU nurses were selected by census method from educational hospitals of Guilan University of Medical Sciences in 2017. Research tools were Varjuss professional autonomy and Corely et al. moral distress questionnaires. Data were analyzed using SPSS software version 16. Results: Most of the subjects were female (93.89%), full-time nurses (61.67%), with age mean and standard deviation of 35±5.97. Mean and standard deviation of professional autonomy and moral distress were 77.04±4 and 140.85±5.45, respectively. Moral distress of most nurses (55.6%) was moderate. There was a positive and significant correlation between professional autonomy and moral distress scores (p<0.001, r=0.33). Conclusion: This study showed that by increasing the professional autonomy, the moral distress of ICU nurses increases as well. These results, by informing nursing mangers, remind the necessity of using some approaches for reducing the moral distress of nurses along with improving their professional autonomy.